Molecular data infers the involvement of a marine aurantiactinomyxon in the life cycle of the myxosporean parasite Paramyxidium giardi (Cnidaria, Myxozoa). Issue 12 (15th July 2019) - Rocha, S.; Alves, Â.; Antunes, C.; Azevedo, C.; Casal, G.
Abstract: An aurantiactinomyxon type is described from the marine naidid Tubificoides pseudogaster (Dahl, 1960), collected from the lower estuary of a Northern Portuguese River. This type constitutes the first of its collective group to be reported from Portugal, and only the fourth described from a marine oligochaete worldwide. Extensive morphological comparisons of new aurantiactinomyxon isolates to all known types without available molecular data are proposed to be unnecessary, given the artificiality of the usage of morphological criteria for actinosporean differentiation and the apparent strict host specificity of the group. Recognition of naidid oligochaetes as the hosts of choice for marine types of aurantiactinomyxon and other collective groups, suggests that the family Naididae played a preponderant role in the myxosporean colonization of estuarine communities. Molecular analyses of the type in study further infer its involvement in the life cycle of Paramyxidium giardi (Cépède, 1906) Freeman and Kristmundsson, 2018, a species that infects the kidney of European eel Anguilla anguilla (Linnaeus, 1758) and that has been reported globally, including from Portuguese waters. The low intraspecific difference registered in relation to Icelandic isolates of P. giardi (0.6%) is hypothesized to result from the emergence of genotypically different subspecies due to geographic isolation.